2022
DOI: 10.3390/jfb13040181
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Membrane–Encapsulated MSNs Loaded with SS31 Peptide Alleviate Myocardial Ischemia-Reperfusion Injury

Abstract: Clinically, antioxidant therapy is a potential strategy for myocardial ischemia-reperfusion injury (MI/RI), a common complication of acute myocardial ischemia. The H-D-Arg-Dmt-Ly-Phe-NH2 (SS31) peptide is shown to have amazing antioxidant properties, but its utilization is limited by the peptide characteristics, such as the destruction by proteases and rapid metabolism. Silica nanoparticles (MSNs) comprise an excellent material for peptide delivery, owing to the protection effect relating to peptides. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…The ratio of the covered area to the sown area of crops negatively impacted AEE. Still, it did not pass the significance test, which was consistent with the conclusion of previous studies (Zhang, 2018;Zhang et al, 2022). Crop planting structure significantly improved AEE in the moderate development region but failed to pass the significance test in the other two regions.…”
Section: Analysis Of Other Influencing Factorssupporting
confidence: 89%
See 3 more Smart Citations
“…The ratio of the covered area to the sown area of crops negatively impacted AEE. Still, it did not pass the significance test, which was consistent with the conclusion of previous studies (Zhang, 2018;Zhang et al, 2022). Crop planting structure significantly improved AEE in the moderate development region but failed to pass the significance test in the other two regions.…”
Section: Analysis Of Other Influencing Factorssupporting
confidence: 89%
“…Adopting the geographical detector model (Wang et al, 2021c) detected that rural residents' income was an important driving factor of AEE spatial differentiation. Based on the panel Tobit model, Zhang et al (2022) found that rural residents' income positively impacted AEE in Hunan, which was consistent with the conclusion obtained in a research on Henan province (Yan et al, 2022). With the increase in rural residents' disposable income by 100 CNY (China yuan), AEE increased by 9.5% (Liu et al, 2020b).…”
Section: Literature Reviewsupporting
confidence: 88%
See 2 more Smart Citations
“…This strategy effectively delivered SS31 peptide to the damaged heart site to exert antioxidant function. 219 In addition, researchers have delivered non-selective b-blockers (Carvedilol), tissue fibrinogen activator (tPA), and CSCs-derived secretome by platelet membrane-coated nanoparticles for treating MI. 220 5.2.2 Stem/progenitor cell membrane-camouflaged nanoparticles.…”
Section: Prospective Future Of MI Therapy Using Cell-derived Nanopart...mentioning
confidence: 99%